Knowledge of Cardiopulmonary Resuscitation Among Interns Working at Kathmandu Medical College - Thapa, Rashmi; Chhetri, Dinesh; Karn, Roshan; Dhakal , Manisha; Chhetri, Mamta; KC, Purba; Thapaliya, Pooja (Journal of Karnali Academy of Health Sciences, 2021)
Background: Cardiac arrest is a substantial public health problem estimated to account for 15-20% of all death. Cardiac arrest is one of the most common emergencies within the emergency department leading to serious and life-threatening results which can be managed if medical and paramedical personnel working in the emergency department have adequate knowledge about cardiopulmonary resuscitation (CPR) and if they are well trained to administer it effectively. Objective: To assess the knowledge, attitude and practice regarding CPR amongst interns in tertiary medical center of Nepal and comprehend the depth of knowledge about CPR and practice regarding defibrillation used during CPR.Methodology: This is a cross-sectional study carried out in Kathmandu Medical College Teaching Hospital using a semi structured pretested questionnaire. We requested interns to answer the questionnaire, which included 25 questions to assess the knowledge of BLS. Similarly, subjects were inquired about the attitude level questionnaire by the researcher and scoring was done accordingly. We analyzed the statistics through frequency, percentage, mean and mean percent.Results: Out of 150 interns, regarding knowledge, on an average 11.71 questions were correctly answered. Highest score of 22 was scored by five participants and lowest of 5 scored by seven participants. Eleven questions were rightly answered by more than 50%. All the participants agreed that resuscitation training need to be added in the curriculum.Conclusion: The present study identified the attitude score was good however, knowledge score of BLS was poor among medical interns. BLS training should be the part of the MBBS curriculum to solve this very critical issue. The unconsolidated knowledge about resuscitation among the interns is not adequate. This study emphasizes the necessity for standardized systemic resuscitation program in the undergraduate curriculum and effort should be made to introduce an appropriate, efficient and effective course design.